Forensic Linguistic in Online Business - Yunita Suryani; Agus Wardhono; Syehfani Alif Akbar; Suantoko Suantoko (Pioneer: Journal of Language and Literature, 2023)
Forensic linguistics is a science that examines language in relation to legal science as a device for proving judicial cases. Forensic linguistics in online business in this study was found in online buying and selling accounts that sell illegal products or are categorised as non-halal. Products are presented in the form of images and descriptions that use language. The sale and purchase are criminal acts of violating the ITE (Informasi dan Teknologi Elektronik or Electronic Information and Technology) Law regarding online transactions. The purpose of the study is to describe linguistic forensics in online business in buying and selling transactions using the persuasive theory of Keraf (1994), including rationalization, identification, suggestion, conformity, compensation, substitution, and projection. For this purpose, the qualitative descriptive research method has been employed. The results of the study indicate violations of the ITE Law related to online buying and selling of mustika (gemstone or talisman) products or talismans in the form of agate.